Pengaruh Motivasi, Kepemimpinan Dan Lingkungan Kerja Terhadap Komitmen Organisasi di Yayasan Al Bayan Hidayatullah Makassar - Erwin; Nujum, Syamsu; St. Nurhayati Aziz (STIM-LPI Makassar, 2025)
This study aims to determine and analyze the influence of motivation, leadership, and the work environment on organizational commitment at the Al Bayan Hidayatullah Foundation in Makassar. Multiple regression analysis was used. Sampling was conducted using the Slovin technique, involving 55 respondents from a population of 122 employees. The results indicate that motivation, leadership, and the work environment have a positive and significant effect on organizational commitment. Motivation has a partial positive and significant effect on organizational commitment, leadership has a partial positive and significant effect on organizational commitment, and work environment has a partial positive and significant effect on organizational commitment at the Al Bayan Hidayatullah Foundation in Makassar.